2021
DOI: 10.3892/mmr.2021.12281
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TCF3 in Wilms' tumor and its regulatory role in kidney tumor cell viability, migration and apoptosis in vitro

Abstract: Wilms' tumor (WT) is a major type of kidney cancer in children; however, the therapeutic measures for control of tumor metastasis, recurrence and death for this type of cancer remain unsatisfactory. The present study aimed to verify the expression of T-cell factor 3 (TCF3) in WT, and to explore its role in regulating the viability, migration and apoptosis of kidney tumor cells. Tumor tissues were collected from 10 patients with WT, and adjacent tissues were collected as normal controls. The expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Novel biomarkers, therefore, are urgently needed in order to predict patients' prognosis and develop novel target-specific therapies. But the introduction of biology-driven approaches to risk stratification and new drug development has been slower in Wilms tumor than in other childhood tumors (7).It is very important to improving prognosis for Wilms tumor patients by improving treatment based on clinical and biological risk factors, and further stratification of current treatment options based on tumor biology (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…Novel biomarkers, therefore, are urgently needed in order to predict patients' prognosis and develop novel target-specific therapies. But the introduction of biology-driven approaches to risk stratification and new drug development has been slower in Wilms tumor than in other childhood tumors (7).It is very important to improving prognosis for Wilms tumor patients by improving treatment based on clinical and biological risk factors, and further stratification of current treatment options based on tumor biology (6,8).…”
Section: Introductionmentioning
confidence: 99%
“…They were then stained with 3,3-diaminobenzidine (DAB, DA1015; Solarbio), counterstained with hematoxylin (G1140; Solarbio) for 5 min at room temperature and mounted with neutral gum after dehydration. 44 All slides were observed by a blinded investigator under a light microscope. Brown staining indicated immunoreactive (positive) cells; blue staining indicated nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that TCF3 is related to the development and progression of many human cancers, such as lung cancer [8],hepatocellular carcinoma [9],prostatic cancer [10],breast cancer [11],cervical carcinoma [12],nephroblastoma [13]and leukemia [14]. It has been reported that TCF3 is a common target of chromosome translocation in acute lymphoblastic leukemia, with multiple companion genes (PBX1, HLF, FB1) fused with TCF3 [14].…”
Section: Introductionmentioning
confidence: 99%